Empowering Skills in Aromatherapy: A Training Program for Massage Oil and Roll-On Product Creation in Cendana Putih Village, Mappedeceng District, North Luwu Regency - Hurria; Alfian, Anggra; Muslimin, Muh. Ashar; Mursyid, Murni; Umar, Anugrah (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
The use of plants for aromatherapy has a long-standing tradition. One common application is the creation of massage oils and roll-on products made from essential oils. When inhaled or applied to the skin, essential oils can stimulate the sensory system, helping to alleviate symptoms of headaches and migraines and promote relaxation. This community service initiative aimed to empower residents to create simple products using essential oils from local plants. The activity took place in June 2025 in Cendana Putih Village, located in the Mappadeceng District of North Luwu Regency, and involved participation from village officials and community members. As a result of this initiative, massage oils and roll-on products were developed using various essential oils.